2022
DOI: 10.1186/s13731-022-00206-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between faculty characteristics and their entrepreneurial orientation in higher education institutions in Kuwait

Abstract: Considering intrapreneurship theory, this study aims to examine the extent to which the entrepreneurial orientation of faculty employed at Kuwaiti higher education institutions differ across their individual-level attributes. Faculty entrepreneurial orientation will be assessed at three levels, i.e., innovativeness, risk-taking, and proactivity. For this purpose, we surveyed a sample of 291 faculty from Kuwaiti colleges and universities. The core constructs were operationalized using scales validated in previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The findings related to the reality of entrepreneurship in policies and regulations indicated that the university in its strategy has no effective policies on the importance of being an entrepreneurial university, although the university's strategic plan includes a future vision and a clear message towards an entrepreneurial university. While the PPU should focus more on forming a bank for entrepreneurial ideas that result from the research (Abidi et al, 2022), the incubator available at the university is highly sought to establish productive or service projects that are in line with the community's needs. The PPU aims to consider the complementary relationship between the university, the businesses, society, and environment, and the government, this result is likely to be consistent with other previous studies (Abdel Wahab, 2018;Carayannis & Rakhmatullin, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings related to the reality of entrepreneurship in policies and regulations indicated that the university in its strategy has no effective policies on the importance of being an entrepreneurial university, although the university's strategic plan includes a future vision and a clear message towards an entrepreneurial university. While the PPU should focus more on forming a bank for entrepreneurial ideas that result from the research (Abidi et al, 2022), the incubator available at the university is highly sought to establish productive or service projects that are in line with the community's needs. The PPU aims to consider the complementary relationship between the university, the businesses, society, and environment, and the government, this result is likely to be consistent with other previous studies (Abdel Wahab, 2018;Carayannis & Rakhmatullin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is insightful for policymakers in Kuwaiti educational institutions. In particular, entrepreneurial engagement for faculty is no less important than establishing internationally accredited schools (Abidi et al, 2022). Abu Labhan (2018) defines the EU as the university that adopts a comprehensive approach to achieve economic and social development at the national and regional levels by preparing a generation of entrepreneurs with work opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…An essential factor in an entrepreneur's success, the entrepreneurial orientation notion has gained prominence in recent years (Etemad, 2022). Characteristics of an entrepreneur include creative problem-solving, initiative, and a willingness to take calculated risks (Kreiser & Davis, 2010;Abidi et al, 2022). Prior research has only found the entrepreneurial orientation idea to be useful in describing entrepreneurs or business performance (Linton, 2019).…”
Section: Teacher's Entrepreneurial Orientationmentioning
confidence: 99%
“…Prior research has only found the entrepreneurial orientation idea to be useful in describing entrepreneurs or business performance (Linton, 2019). However, modern teachers often work in fields where they bear sole responsibility for outcomes (Abidi et al, 2022). In addition, as teachers typically undertake innovative or rarely repeated activities, they are typically given considerable latitude in how they go about their daily work.…”
Section: Teacher's Entrepreneurial Orientationmentioning
confidence: 99%
“…Entrepreneurship activities are being emphasized in many sectors of national economies worldwide, including the education sector (Abidi et al, 2022). A major activity associated with entrepreneurship, including entrepreneurial marketing, is research (academic and applied).…”
Section: Entrepreneurship Marketing Researchmentioning
confidence: 99%